2022
DOI: 10.7759/cureus.31806
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bioceramic Putty in Pulpotomy of Immature Permanent Molars With Symptoms of Irreversible Pulpitis

Abstract: This study aimed to evaluate the effectiveness of both mineral trioxide aggregate (MTA) and bioceramic putty (Well-Root PT) in the pulpotomy of immature permanent molars diagnosed with symptoms of irreversible pulpitis. Materials and methodsThe study included 30 immature permanent molars with symptoms of irreversible pulpitis in 30 healthy children aged six to eight years. They were randomly distributed into the following two groups according to the material used: group 1 included 15 first permanent molars cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this study, ECZr and WPT did not form a detectable amount of hydroxyapatite in vivo, while PR did. The differences in apatite-forming ability may explain the less favorable outcomes of ECZr and WPT compared with the outcomes using PR in vital pulp therapy [33,34]. Additionally, we showed that MTAHP, EMTA, WST, BioCR, and MTAF also did not form a detectable amount of hydroxyapatite in rat subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, ECZr and WPT did not form a detectable amount of hydroxyapatite in vivo, while PR did. The differences in apatite-forming ability may explain the less favorable outcomes of ECZr and WPT compared with the outcomes using PR in vital pulp therapy [33,34]. Additionally, we showed that MTAHP, EMTA, WST, BioCR, and MTAF also did not form a detectable amount of hydroxyapatite in rat subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, ECZr and WPT did not form a detectable amount of hydroxyapatite in vivo, while PR did. The differences in apatite-forming ability may explain the less favorable outcomes of ECZr and WPT compared with the outcomes using PR in vital pulp therapy [55,56]. Additionally, we showed that MTAHP, EMTA, WST, and BioCR also did not form a detectable amount of hydroxyapatite in rat subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 78%
“…Following a one-year follow-up, bioceramic putty demonstrated a clinical and radiographic success rate of 93.4%, with only one case of failure. Meanwhile, MTA exhibited a 100% success rate both clinically and radiographically after a one-year evaluation period [ 31 ].…”
Section: Discussionmentioning
confidence: 99%